Perancangan Aplikasi Dokumen Elektronik Terintegrasi dalam Pengelolaan Dokumen Klaim BPJS Kesehatan pada Era SEP Elektronik - Heru Rahmat Wibawa Putra; Adri Yanto (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Digital transformation in the health sector drives the need for efficiency in document management, especially for BPJS Kesehatan claims. Manual processes often cause delays and the risk of losing documents. Therefore, this study aims to design an integrated electronic document application to overcome these problems. This study uses the SDLC Waterfall approach which includes the stages of gathering needs, design, implementation, testing, and maintenance. Data were collected through interviews, observations, and needs analysis at the Ibnu Sina Islamic Hospital, Payakumbuh. The designed application successfully integrates various BPJS Kesehatan claim documents, such as Individual Patient Sheets (LIP), Participant Eligibility Letters (SEP), and laboratory results, into one PDF format automatically. The designed system can help the digital transformation of hospitals and simplify the claim verification process. The integrated electronic document application improves the efficiency and accuracy of BPJS Kesehatan claim document management.